2014 IEEE/ASME International Conference on Advanced Intelligent Mechatronics 2014
DOI: 10.1109/aim.2014.6878268
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Kinematic modeling of a class of continuum bionic handling arm

Abstract: This paper presents a development of Inverse Kinematic Model (IKM) of a class of Continuum Bionic Handling Arm (CBHA). The modeling approach is inspired from a model of a hyper-redundant backbone-based manipulator, combined with an optimal placement of the backbones. The latter is obtained using an optimization algorithm, based on a Sequential Quadratic Program (SQP). The main interest of developing such model is to design an autonomous control of the CBHA. The high number of Degrees of Freedom (DoF) present o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…25,26 Description Robotino-XT, as shown in Figure 14(a), is a mobile robot manipulator based on an omnidirectional robot called Robotino. It is a smaller version of the robot ''Continuum Bionic Handling Assistant.''…”
Section: Experimental Validationmentioning
confidence: 99%
“…25,26 Description Robotino-XT, as shown in Figure 14(a), is a mobile robot manipulator based on an omnidirectional robot called Robotino. It is a smaller version of the robot ''Continuum Bionic Handling Assistant.''…”
Section: Experimental Validationmentioning
confidence: 99%
“…Finally, the elongations of each inter-vertebra are obtained through the IKES. For more details, we refer the interested reader to [27], [29].…”
Section: A Kinematics Of the Soft-continuum Manipulator Cbhamentioning
confidence: 99%
“…Several approaches and methods have been proposed for solving the IKM of continuum robots such as cited in some research works. 4,6,11,20 Knowing that the accuracy of the model depends on the number of considered bending sections, for this case, a metaheuristic approach is proposed in this work. Summing up, the determination of each bending section endpoint that assures the desired task and compatibility with physical constraints of the robot is given in the following section.…”
Section: Determination Of Links' Length Based On Parallel Robot Morphmentioning
confidence: 99%
“…Furthermore, the IKM for multi-section robot with a special configuration has also been proposed by Jones and Walker 4 and Lakhal et al 11 To validate the model suggested in the work, 4 nevertheless the authors 4 have used specific software of symbolic computation to simulate the kinematic behavior of a continuum robot. They also studied the workspace and the configuration area to describe the constraints due to boundary limitations with respect to the lengths of robot.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation